2019
DOI: 10.1038/s41598-019-42260-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metagenomics study reveals pollution induced changes of microbial genes in mangrove sediments

Abstract: Mangrove forests are widespread along the subtropical and tropical coasts. They provide a habitat for a wide variety of plants, animals and microorganisms, and act as a buffer zone between the ocean and land. Along with other coastal environments, mangrove ecosystems are under increasing pressure from human activities, such as excessive input of nutrients and toxic pollutants. Despite efforts to understand the diversity of microbes in mangrove sediments, their metabolic capability in pristine and contaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 69 publications
0
23
1
3
Order By: Relevance
“…These specific signatures are thought to result from microbial adaptation and/or physical selection to the environmental abiotic conditions (Hindré et al, 2012;Li et al, 2019;Rey et al, 2016) and are a reflection of the high relative abundances of genes coding for specific functions essential for microorganisms to survive and develop in these environments. For example, microbial metagenomes of human feces were characterized by high relative abundances of sequences annotated as beta-glucosidases that are associated with high intestinal concentrations of complex glycosides; and microbial metagenomes of oceans were enriched in sequences annotated as enzymes catalyzing DMSP (dimethylsulfoniopropionate), that is an organosulfur compound produced by phytoplankton (Delmont et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These specific signatures are thought to result from microbial adaptation and/or physical selection to the environmental abiotic conditions (Hindré et al, 2012;Li et al, 2019;Rey et al, 2016) and are a reflection of the high relative abundances of genes coding for specific functions essential for microorganisms to survive and develop in these environments. For example, microbial metagenomes of human feces were characterized by high relative abundances of sequences annotated as beta-glucosidases that are associated with high intestinal concentrations of complex glycosides; and microbial metagenomes of oceans were enriched in sequences annotated as enzymes catalyzing DMSP (dimethylsulfoniopropionate), that is an organosulfur compound produced by phytoplankton (Delmont et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, only five metagenomic studies on airborne microbial communities at one or two specific sites per study exist (Aalismail et al, 2019;Amato et al, 2019;Cao et al, 2014;Gusareva et al, 2019;Yooseph et al, 2013). Metagenomic investigations of complex microbial communities in many ecosystems (for example, soil, seawater, lakes, feces, sludge) have provided evidence that microorganism functional signatures reflect the abiotic conditions of their environment, with different relative abundances of specific microbial functional classes (Delmont et al, 2011;Li et al, 2019;Tringe et al, 2005;Xie et al, 2011). This observed correlation of microbial community functional potential and the physical and chemical characteristics of their environments could have resulted from genetic modifications (microbial adaptation) (Brune et al, 2000;Hindré et al, 2012;Rey et al, 2016;Yooseph et al, 2010) and/or physical selection.…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomics was also applied to study the upper and core regions of oxygen minimum zones in Arabian Sea, and confirmed the genomic potentials of active nitrogen cycle [19]. The metagenomic results revealed that the metabolic capacity of microorganisms might be weaken by contamination in mangrove sediments and the increase of greenhouse gas emission might be induced [20]. Recently, combining of 16S rRNA amplicon sequencing and metagenomic shotgun analysis revealed that chemical pollutants severely affected microbial structures and functions in sediments [21].…”
Section: Introductionmentioning
confidence: 83%
“…Por otra parte, estudios como el de Li et al [28] han comprobado que al comparar la capacidad metabólica de los microorganismos presentes en ecosistemas contaminados con fertilizantes y sin contaminar, estos presentan reducción en el pool de genes que les proveen la capacidad de fijar Nitrógeno, mientras que muestran un metabolismo aumentado respecto a la generación de gases de efecto invernadero como el metano o los sulfatos, lo que evidencia cambios en las comunidades y el metabolismo microbiano a causa de este tipo de contaminantes. Fig.…”
Section: Impacto De Los Fertilizantes Nitrogenadosunclassified